ANALISIS PERENCANAAN KEBUTUHAN TENAGA DOKTER OLEH DINAS KESEHATAN KOTA PEKANBARU - marlinda, pebriana (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
This study addresses the need of medical doctors planning process undertaken by theHealth Deparment in Pekanbaru City. So far inventory step in the planning process under taken only limited data collection and the number of qualified doctorsonly, not to the activity analysis and mapping. In addition,the method that used by health office in Pekanbaru City is not standard, so that the number of doctors exceeds national standards, but it is not appropriate qualifications and uneven distribution.This study is a qualitative research to seeks and understand deeply the secondary data from the documents which related the topics, as well as the primary data obtained from interviews with informant of the research as : Chief of medical department, The head of Human resources division and Chief of health section of Health Services and Referral Association.To analyze the planning needs of medical doctors conducted by the Health Departement Pekanbaru city, the author uses the theory proposed by Noatmodjo (2003: 24), namely: inventory, estimate (forecasting), and the planning, monitoring and evaluation.The conclusion of this research is the planning of the medical doctors’ need which has done by health department of Pekanbaru had through steps as follows: inventory, forecasting (estimate), monitoring and evaluation. But there should be strengthened in every steps and also commitment from pekanbaru government, as preparation of the health master plan, minimum standard services, establishes a special a department of planning and standard operational procedure.